Chinese art from the collection of H.M. King Gustaf VI Adolf of Sweden - Gustaf VI Adolf King of Sweden 1882-1973; Gyllensvard, Bo; Pope, John Alexander 1906-1982 (The Asia Society, Inc. ; Distributed by H. N. Abrams, Inc., 1966)
Chinese art is visual art that, whether ancient or modern, originated in or is practiced in China or by Chinese artists or performers. Early so-called "stone age art" dates back to 10,000 BC, mostly consisting of simple pottery and sculptures. This early period was followed by a series of art dynasties, most of which lasted several hundred years. The Chinese art in the Republic of China (Taiwan) and that of overseas Chinese can also be considered part of Chinese art where it is based in or draws on Chinese heritage and Chinese culture.Porcelain is made from a hard paste made of the clay kaolin and a feldspar called petuntse, which cements the vessel and seals any pores. China has become synonymous with high-quality porcelain. Most china pots comes from the city of Jingdezhen in China's Jiangxi province. Jingdezhen, under a variety of names, has been central to porcelain production in China since at least the early Han Dynasty. The most noticeable difference between porcelain and the other pottery clays is that it "wets" very quickly (that is, added water has a noticeably greater effect on the plasticity for porcelain than other clays), and that it tends to continue to "move" longer than other clays, requiring experience in handling to attain optimum results. During medieval times in Europe, porcelain was very expensive and in high demand for its beauty. TLV mirrors also date from the Han dynasty.Early forms of art in China are found in the Neolithic Yangshao culture (Chinese: 仰韶文化; pinyin: Yǎngsháo Wénhuà), which dates back to the 6th millennium BC. Archeological findings such as those at the Banpo have revealed that the Yangshao made pottery; early ceramics were unpainted and most often cord-marked.